Effects of two consecutive matches on the physical demand of elite padel players - Miralles, R.; Martínez-Gallego, R.; Guzmán, J. F.; Ramón-Llin, J. (International Journal of Sports Science & Coaching, 2025)
The aim of this study was to analyse external load variables recorded with inertial devices in elite padel players, comparing results between two matches played consecutively on the same day. A total of 83 male players participated in 23 semifinal and final matches of the professional circuit. Key metrics such as distance travelled, accelerations and decelerations per hour, maximum speeds, and acceleration profiles were recorded. Findings indicated that semifinal matches were more demanding than final matches, with higher values in accelerations, decelerations, and maximum speeds. Notably, 80% of accelerations and decelerations occurred within 1 to 2 meters. Statistical significance was set at ? = 0.05, revealing that acceleration and deceleration counts were significantly higher in the first match of the day (p = 0.04; r = 0.23). These results provide insights into the external load experienced by players, allowing for more precise monitoring and optimization of training and recovery strategies. The study underscores the importance of accounting for match load in training regimens, particularly when multiple matches are scheduled on the same day, to enhance player performance and reduce fatigue-related decline.